2020
DOI: 10.1002/14651858.cd013739
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic anticoagulants for people hospitalised with COVID-19

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) is a serious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The primary manifestation is respiratory insu iciency that can also be related to di use pulmonary microthrombosis in people with COVID-19. This disease also causes thromboembolic events, such as pulmonary embolism, deep venous thrombosis, arterial thrombosis, catheter thrombosis, and disseminated intravascular coagulopathy. Recent studies have indicated a worse prognosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 50 publications
2
51
0
2
Order By: Relevance
“…In our academic hospitals, patients were mostly treated with prophylactic doses of LMWH, whereas intermediate or therapeutic doses were used only in a small group of patients (n = 32, 12.3%). This means that most clinicians strictly adhere to the current international recommendations, based on observational data or information obtained in similar setting of hospitalized patients [ 9 , 10 , 14 , 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our academic hospitals, patients were mostly treated with prophylactic doses of LMWH, whereas intermediate or therapeutic doses were used only in a small group of patients (n = 32, 12.3%). This means that most clinicians strictly adhere to the current international recommendations, based on observational data or information obtained in similar setting of hospitalized patients [ 9 , 10 , 14 , 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of all-cause mortality with prophylactic anticoagulants compared with no prophylaxis was inconsistent among the included studies and the analyses of VTE events were not performed due to the lack of data. 60 Using a pooled analysis, our study quantifies and compares the estimates of these outcomes according to the dosage of pharmacologic thromboprophylaxis, and therefore, adding value to the existing literature. This pooled analysis suggests that standard pharmacologic thromboprophylaxis is effective in preventing total venous thrombotic events during hospitalization compared with no anticoagulation and supports current societal guidance that recommends at least a universal pharmacologic thromboprophylaxis for all hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of all-cause mortality with prophylactic anticoagulants compared with no prophylaxis was inconsistent among the included studies and the analyses of VTE events were not performed due to the lack of data. 60 Using a pooled analysis, our study quantifies and compares the estimates of these outcomes according to the dosage of pharmacologic thromboprophylaxis, and therefore, adding value to the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the ischemic stroke was complicated by a hemorrhagic infarction, possibly fostered by the prophylactic use of heparin [ 40 , 41 , 42 ]. Similarly, another study reported a case of fatal intracranial bleeding in a patient affected by COVID-19 who was treated with heparin [ 27 ].…”
Section: Case Reportmentioning
confidence: 99%